The intracellular growth of the vacuolar pathogen Legionella pneumophila is dependent on the acyl chain composition of host membranes - Wilkins, Ashley A.; Schwarz, Benjamin; Torres-Escobar, Ascencion; Castore, Reneau; Landry, Layne; Latimer, Brian; Bohrnsen, Eric; Bosio, Catharine M.; Dragoi, Ana-Maria; Ivanov, Stanimir S. (Frontiers in Bacteriology, 2024)
Legionella pneumophila is an accidental human bacterial pathogen that infects and replicates within alveolar macrophages causing a severe atypical pneumonia known as Legionnaires' disease. As a prototypical vacuolar pathogen L. pneumophila establishes a unique endoplasmic reticulum (ER)derived organelle within which bacterial replication takes place. Bacteria-derived proteins are deposited in the host cytosol and in the lumen of the pathogen-occupied vacuole via a type IVb (T4bSS) and a type II (T2SS) secretion system respectively. These secretion system effectors manipulate host functions to facilitate intracellular survival. Subversion of host membrane glycerophospholipids (GPLs) by the internalized bacteria via distinct mechanisms feature prominently in trafficking and biogenesis of the Legionella-containing vacuole (LCV). Conventional GPLs composed of a glycerol backbone linked to a polar headgroup and esterified with two fatty acids constitute the bulk of membrane lipids in eukaryotic cells. The acyl chain composition of GPLs dictates phase separation of the lipid bilayer and therefore determines the physiochemical properties of biological membranes -such as membrane disorder, fluidity and permeability. In mammalian cells, fatty acids esterified in membrane GPLs are sourced endogenously from de novo synthesis or from the exogenous pool of lipids present in interstitial fluids. We exploited the preferential utilization of exogenous fatty acids for GPL synthesis by macrophages to reprogram the host membranes and investigated its impact on LCV homeostasis and L. pneumophila intracellular replication. Using saturated fatty acids as well as cis and trans-isomers of monounsaturated fatty acids we discovered that under conditions promoting lipid packing and membrane rigidification L. pneumophila intracellular replication was significantly reduced. Palmitoleic acid -a C16:1 monounsaturated fatty acid -that promotes membrane disorder when enriched in GPLs significantly increased bacterial replication within human and murine macrophages but not in axenic growth assays. Lipidome analysis of infected macrophages showed that treatment with exogenous palmitoleic acid resulted in membrane acyl chain reprogramming in a manner that promotes membrane disorder and live-cell imaging revealed that the consequences of increasing membrane disorder impinge on several LCV homeostasis parameters. Collectively, we provide experimental evidence that L. pneumophila replication within its intracellular niche is a function of the lipid bilayer disorder and hydrophobic thickness.